Evaluation of the Antifungal Activity of Five Medicinal Plants on the In vitro Growth of a Multi-resistant Strain of Candida albicans - N’dri Ange, Konan Gbê Kouakou; Sitapha, Ouattara; Yao, Kanga; Urbain, Monney Yapo; Mathieu, Kra Adou Koffi (European Scientific Journal, ESJ, 2023)
This paper focuses on determining the antifungal potential of plants traditionally used to treat infections. Five (5) plants were collected. The anti-Candida albicans activity was evaluated by the double dilution method in tilted tubes with the aqueous and hydroethanolic extracts of the different plants. The results showed that 70% ethanolic extracts were more active than the aqueous extracts for all the plants. The 70% ethanolic extract of Terminalia ivorensis (MFC = 1.56 mg/mL) was the most active on the tested strain. This was followed by Terminalia Superba (MFC = 3.125 mg/mL), Distemonanthus benthamianus (MFC = 50 mg/mL), Gmelina arborea (MFC= 50 mg/mL), and Justicia secunda (MFC ˃ 50 mg/mL). The phytochemical screening revealed the presence of seven (7) major groups of compounds. Saponosides are present only in the aqueous extracts of plants. Polyphenols, Flavonoids, Polyterpenes, and Sterols as well as Tanins are present in both alcoholic and aqueous extracts. These compounds could justify its activity and its traditional use. The interesting results obtained with the hydroethanolic extract of Terminalia ivorensis incite further research with this extract. A bio-guided study on the fractions from this extract could lead to the discovery of one or more molecules of interest in the fight against pathogenic fungi.